Integrated performance management : a guide to strategy implementation - Verweire, Kurt; Berghe, L. van den (Lutgart), 1951- (Sage, 2004)
Linking various disciplines and management functions, Integrated Performance Management provides the reader with a concrete framework to manage organizations successfully. The authors do not isolate a single strategy to manage performance. Instead, the book focuses on a range of strategies providing the reader with an introduction to each one.